Dinamika Penerimaan Mahasiswa PTKIN Terhadap Lagu Mars Shubbanul Wathan di Acara Pengenalan Budaya Akademik Kampus - Aly Mashar (Universitas Islam Tribakti Lirboyo Kediri, 2023)
This study investigated the reception or response of students participating in the 2018 IAIN Surakarta Academic and Student Guidance Program (PBAK) to the Shubbanul Wathan March Song (LMSW). These students come from various backgrounds of different religious organizations, and this study aims to analyze how they receive the dominant meaning in the LMSW text as well as the factors that influence their reception of the song. The approach used in this research is qualitative and descriptive; however, it also utilizes quantitative data. Reception analysis was used as the theoretical framework and analysis in this study. The research was conducted at IAIN Surakarta from May 3, 2019, to September 30, 2019, with the research subjects being students participating in PBAK IAIN Surakarta in 2018. The results of this study revealed the following. First, PBAK students accept the dominant meaning of the LMSW text, which includes aspects of nationalism, love for the country, and the spirit of state defense. However, they also placed the song in opposition to some of the meanings advocated by the PBAK committee. Students believe that the inclusion of LMSW as a compulsory song in PBAK is not an appropriate action because PBAK and IAIN Surakarta as state institutions are expected to remain neutral from the affiliation of certain religious organizations, while LMSW is known as a song belonging to Nahdlatul Ulama. Second, opposition to this meaning is influenced by the religious background of each student, with the main factor being their lack of understanding of the LMSW's position as the National Anthem. Their rejection is based on the assumption that LMSW is associated more with Nahdlatul Ulama than with national identity.